2017
DOI: 10.1371/journal.pone.0170667
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Two Real-Time PCR Assays for Chronic Hepatitis C Patients Receiving Protease Inhibitor-Based Therapy

Abstract: The aim of this study was to determine the efficacy of two hepatitis C virus (HCV) real-time PCR assays, the COBAS AmpliPrep/COBAS TaqMan HCV test (CAP/CTM) and the Abbott RealTime HCV test (ART), for predicting the clinical outcomes of patients infected with HCV who received telaprevir (TVR)-based triple therapy or daclatasvir/asunaprevir (DCV/ASV) dual therapy. The rapid virological response rates in patients receiving TVR-based triple therapy were 92% (23/25) and 40% (10/25) for CAP/CTM and ART, respectivel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
1
3
0
Order By: Relevance
“…Subsequent studies reported that W4VLs were undetectable in only 10%‐14% using the Abbot assay and 51%‐55% using the Roche assay among genotype 1‐infected patients treated with SMV+SOF±RIBA or daclatasvir+SOF, which is closer to our finding of 23.5% (Abbott) and 39.4% (Roche) undetectable W4VL. Taken together with these studies, our findings suggest that DAQ and DBQ at W4VL is a common occurrence that merits further study, and that it is much more common with the Abbott than with the Roche assays, as demonstrated by two other recent studies . Whether the higher positivity rate of the Abbott relative to the Roche assay is due to a greater true‐positive rate or a greater false‐positive rate or both remains to be determined.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Subsequent studies reported that W4VLs were undetectable in only 10%‐14% using the Abbot assay and 51%‐55% using the Roche assay among genotype 1‐infected patients treated with SMV+SOF±RIBA or daclatasvir+SOF, which is closer to our finding of 23.5% (Abbott) and 39.4% (Roche) undetectable W4VL. Taken together with these studies, our findings suggest that DAQ and DBQ at W4VL is a common occurrence that merits further study, and that it is much more common with the Abbott than with the Roche assays, as demonstrated by two other recent studies . Whether the higher positivity rate of the Abbott relative to the Roche assay is due to a greater true‐positive rate or a greater false‐positive rate or both remains to be determined.…”
Section: Discussionsupporting
confidence: 76%
“…Taken together with these studies, our findings suggest that DAQ and DBQ at W4VL is a common occurrence that merits further study, and that it is much more common with the Abbott than with the Roche assays, as demonstrated by two other recent studies. 23,24 Whether the higher positivity rate of the Abbott relative to the Roche assay is due to a greater true-positive rate or a greater false-positive rate or both remains to be determined. Many baseline characteristics that are negative predictors of SVR were also found to be predictors of positive W4VL as might be expected, such as genotype 3 HCV, baseline viral load >6 million IU/mL, Black race, cirrhosis, low platelet count and other laboratory markers of liver dysfunction.…”
Section: Sustained Virologic Response In Patients With Genotype 1 Hmentioning
confidence: 99%
“…12 It was reported that HCV kinetics differed, between the COBAS AmpliPrep/COBAS TaqMan HCV test used in this study and the Abbott Real-time HCV test (ART, Abbott Diagnostics, Lake Forest, IL, USA). 13,14 In conclusion, the reduction in serum HCV-RNA levels 1 day after the start of anti-HCV IFN-free regimens with DAAs was not correlated with any patient characteristics except for liver fibrosis. This reduction was associated with virologic outcomes in patients receiving 12-week regimens and was predictive of SVR and is thus a potential factor for identifying patients at risk of treatment failure.…”
Section: Discussionmentioning
confidence: 81%
“…In addition, differences between assays for HCV‐RNA quantification need to be considered . It was reported that HCV kinetics differed, between the COBAS AmpliPrep/COBAS TaqMan HCV test used in this study and the Abbott Real‐time HCV test (ART, Abbott Diagnostics, Lake Forest, IL, USA) …”
Section: Discussionmentioning
confidence: 99%